Percutaneous transcatheter intervention in a cyanotic congenital heart disease at tertiary care hospital in Western Rajasthan: a single centre experience - Mathur, Rohit; Gupta, Deepak; Kumar, Goutam; Sanghvi, Sanjeev; Baroopal, Anil (International Journal of Research in Medical Sciences, 2017)
Background: Treatment of congenital heart disease (CHD) is either surgical or interventional. Medical management is mainly symptomatic or palliative. Although surgery is the main mode of treatment but in the recent past non-surgical interventional method is replacing it because of its multiple advantages over surgical procedures. In this article, we report the success rate of the percutaneous transcatheter device closure procedures in our tertiary care hospital. Methods: The aim of this study is to review the short-term outcome of the non-surgical interventional treatment of congenital heart diseases. We included percutaneous transcatheter device closure of atrial septal defect (ASD), ventricular septal defect (VSD), patent ductus arteriosus (PDA) and ruptured sinus of valsalva aneurysm (SVA) performed at our hospital between September 2014 and November 2016. Results: We performed total 28 cases of ASD device, 3 cases of VSD device, 12 cases of PDA device, 2 cases of ruptured SVA device closures. Almost all our intervention procedures were successful except two cases of failure of ASD closure. There was no mortality and major complication related to procedures. All patients of successful interventional treatment are enjoying new life without any morbidity. Conclusions: Percutaneous transcatheter device closure for suitably selected cases of a cyanotic CHDs including ASD, VSD, PDA and ruptured SVA may be an alternative, lucrative, safe and effective option with least morbidity and mortality.